Identification of environmentally sensitive areas (soil) for forest management in Sarawak - Sia, Puon Chiew. (2002)
Malaysia has included the identification of enviromentally sensitive areas (ESAs) as an indicator in the Malaysian Criteria, Indicators, activities and Standards of Performance (MC&I) but a practical cost-effective and labour-efficient method of identification is yet to be established in Sarawak. Three existing approaches to identifying ESAs (soil) were discussed. The USLE in a GIS environment is an easy, distributed approach but is not most suited for application to the dissimilar rainfall, soil and terrain conditions of Sarawak. An approach involving recognizing indicative features from maps and aerial photos is desirable but hampered by the ften unavailability of up-to-date quality aerial photos in Sarawak. Landslide susceptibilty rating also requires intensive ground survey.